Artificial graphite, preparation method and negative pole piece
By pulverizing the artificial graphite precursor at a lower temperature, forming a graphite layered structure and doping elements to adjust the layer spacing, the problem of high temperature and high energy consumption of graphitization treatment in the prior art is solved, and the electrical performance and specific capacity of artificial graphite are improved.
Patent Information
- Application Number
- CN202411852825.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-29
AI Technical Summary
In the existing artificial graphite preparation methods, graphitization treatment requires high temperature heat treatment above 2000°C, resulting in high energy consumption and difficult process, which limits the application performance of artificial graphite in battery negative electrode materials.
By subjecting the ionic liquid to a suitable temperature treatment, an artificial graphite precursor was obtained and pulverized at a lower temperature of 250°C-1200°C, the carbon atoms were rearranged to form a graphite layered structure, and the graphite layer spacing was adjusted by doping elements.
The process difficulty and preparation cost of artificial graphite production are reduced, the specific capacity and cyclic performance of artificial graphite are improved, and the specific capacity and cycling performance of artificial graphite are improved, so that it has excellent electrical performance and fast charging performance as a battery negative electrode material.
Smart Images

Figure CN119898766A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery negative electrode materials, and specifically, to artificial graphite and a preparation method thereof, and a negative electrode sheet. Background Art
[0002] As the requirements for battery life in electric vehicles and mid-to-high-end electronic products continue to increase, the battery industry has also developed rapidly. Carbon-based materials are currently the most commonly used negative electrode materials due to their abundant sources. Carbon-based materials can be mainly divided into natural graphite, artificial graphite, soft carbon, hard carbon, etc. Among them, artificial graphite is a graphite material obtained by organic carbonization and then graphitization high-temperature treatment. Compared with natural graphite, artificial graphite usually has a higher degree of graphitization and better structural stability.
[0003] The preparation of artificial graphite mainly includes the following key steps: crushing, granulation, graphitization, screening and demagnetization, and packaging inspection. Among them, graphitization is the key process in the production of artificial graphite. Because the graphitization process requires high-temperature heat treatment above 2000°C, the energy consumption cost is high and the process is difficult. Therefore, in the current artificial graphite manufacturing cost structure, the cost of the graphitization step can reach 50% of the total cost, which is the bottleneck link that limits the further reduction of the artificial graphite manufacturing cost. The preparation method of artificial graphite in the related art is difficult to control the structural defects of artificial graphite, thereby limiting the performance of artificial graphite in the application of battery negative electrode materials. The method for preparing artificial graphite proposed in this application can make the carbon source material complete atomic rearrangement and structural transformation at a lower graphitization temperature, and the prepared artificial graphite also has good specific capacity and cycle performance. Summary of the invention
[0004] In the first aspect of the present application, the present application proposes a method for preparing artificial graphite, comprising: subjecting an ionic liquid to a suitable temperature treatment to obtain an artificial graphite precursor; subjecting the artificial graphite precursor to a pulverizing treatment to obtain the artificial graphite, wherein the nitrogen doping amount in the artificial graphite is 0.5wt%-6wt%, and the phosphorus doping amount is 1wt%-9wt%.
[0005] Therefore, the method for preparing artificial graphite proposed in the present application causes structural rearrangement of carbon atoms at a relatively low temperature of 250°C-1200°C to form a layered structure corresponding to graphite, and adjusts the graphite interlayer spacing through hybridization of doped element atoms, thereby reducing the process difficulty and preparation cost of artificial graphite production, and having a higher specific capacity as a battery negative electrode.
[0006] In some embodiments, the temperature of the temperature-appropriate treatment is 600° C.-1000° C. Thus, the temperature-appropriate treatment conditions can provide energy for the rearrangement of carbon atoms and doping atoms, so as to form a three-dimensional ordered structure of graphite.
[0007] In some embodiments, the ionic liquid includes at least one of imidazole ionic liquid, pyridine ionic liquid, quaternary ammonium ionic liquid, quaternary phosphine ionic liquid, pyrrolidine ionic liquid, and piperidine ionic liquid. Thus, the ionic liquid can be used as a carbon source material for artificial graphite and as a source material for doping elements.
[0008] In some embodiments, the imidazole ionic liquid includes at least one of 1-methylimidazolium chloride, 1-methylimidazolium tetrafluoroborate, and N-methylimidazolium bis(trifluoromethanesulfonyl)imide. Thus, the cation of the imidazole ionic liquid can provide a carbon ring structure, and the anion can provide a doping element atom.
[0009] In some embodiments, the pyridinium ionic liquid includes at least one of N-ethylpyridinium chloride, N-ethylpyridinium hexafluorophosphate, propylpyridinium chloride, and N-butylpyridinium acetate. Thus, the cation of the pyridinium ionic liquid can provide a carbon ring structure for preparing artificial graphite, and the anion can provide doping element atoms.
[0010] In some embodiments, the temperature treatment is heated to a constant temperature, wherein the temperature increase rate of the temperature treatment is 1°C / min-5°C / min. Thus, the temperature increase rate of the temperature treatment is within the aforementioned range, which can achieve the perfect development of the graphite layered stacking structure.
[0011] In some embodiments, the temperature treatment is heated to a constant temperature, wherein the temperature treatment is maintained at a constant temperature for 2 hours to 4 hours. Thus, artificial graphite with an ordered three-dimensional structure can be prepared.
[0012] In some embodiments, after the pulverization process, the Dv50 particle size of the artificial graphite is 9 μm-13 μm. Thus, the particle size of the prepared artificial graphite is within the aforementioned range, and it has a higher compaction density as a negative electrode material for a battery.
[0013] In some embodiments, the method further comprises: before the temperature treatment, mixing the ionic liquid with a coke material, wherein the mass ratio of the ionic liquid to the coke material is (1-5):1, and the coke material comprises at least one of coal-based coke, oil-based coke, and bio-based carbon material. Thus, the amount of ionic liquid in the carbon source material can be reduced, and the manufacturing cost of artificial graphite can be controlled.
[0014] In some embodiments, the method further comprises: purifying the coke material before mixing the ionic liquid with the coke material. Thus, the structure of the prepared artificial graphite can be controlled and optimized.
[0015] In some embodiments, the mixing process includes ball milling, wherein the rotation speed of the ball milling is 400 rpm-800 rpm, and the mixing time is 1 h-3 h, thereby enabling the different carbon source materials to be fully mixed.
[0016] In a second aspect of the present application, the present application proposes an artificial graphite, which is prepared by the method proposed in the present application.
[0017] The artificial graphite proposed in the present application has a relatively regular three-dimensional structure and a relatively balanced particle size distribution, and has a good specific capacity as a battery negative electrode material.
[0018] In the third aspect of the present application, the present application proposes a negative electrode plate, comprising: the artificial graphite described in the application.
[0019] The negative electrode plate comprises a negative electrode current collector and a negative electrode material layer, wherein the negative electrode material layer comprises the artificial graphite described in the present application. Therefore, the negative electrode plate proposed in the present application has good electrical performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0021] Figure 1 A flow chart of preparing artificial graphite in one embodiment of the present application;
[0022] Figure 2 A flow chart of manufacturing artificial graphite in another embodiment of the present application;
[0023] Figure 3 This is the 0.1C charge and discharge curve of the button battery prepared with artificial graphite in Example 1 of the present application. DETAILED DESCRIPTION
[0024] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0025] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0026] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0027] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0028] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0029] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0030] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0031] In the first aspect of the present application, the present application proposes a method for preparing artificial graphite, referring to Figure 1 , including: performing temperature treatment on the ionic liquid to obtain an artificial graphite precursor; performing crushing treatment on the artificial graphite precursor to obtain the artificial graphite, wherein the nitrogen doping amount in the artificial graphite is 0.5wt%-6wt%, and the phosphorus doping amount is 1wt%-9wt%.
[0032] Therefore, the method for preparing artificial graphite proposed in the present application utilizes the weak inter-ionic force and loose structure of ionic liquids to realize the orderly transformation of thermodynamically unstable carbon atoms from a chaotic layer structure to a graphite crystal structure at a lower temperature and less energy supply, so that the carbon atoms undergo structural rearrangement to form a layered structure corresponding to graphite. The imidazolium cation, pyridinium cation, etc. in the ionic liquid can provide nitrogen elements, and the dihydrogen phosphate ion (H 2 PO 4 - ), phosphate ion (PO 4 3- ), hexafluorophosphate (PF 6 - ) and the like can provide phosphorus. Furthermore, the temperature of the proper temperature treatment is 250°C-1200°C, and the lower the temperature of the proper temperature treatment is, the higher the doping amount of nitrogen and phosphorus in the obtained artificial graphite is. By controlling the temperature of the proper temperature treatment, the imidazole ring and pyridine ring in the ionic liquid act as soft templates, inducing the surrounding C atoms to rearrange and form a graphitized structure, and the nitrogen atoms tend to be retained on the graphite ring structure in the form of pyridine-N, pyrrole-N and graphite-N. In the process of rearrangement, the phosphorus element on the anion is doped on the graphite plane in the form of a PC bond, which can make the nitrogen and phosphorus elements in the appropriate amount of the ionic liquid also enter the ordered structure of the artificial graphite at high temperature, form chemical bonds, and hybridize as doping element atoms, thereby adjusting the graphite layer spacing, so that the artificial graphite increases the spacing, which is more conducive to the deintercalation of ions when used as the negative electrode of the battery, and provides more ion sites, so that it has a higher specific capacity as the negative electrode material of the battery.
[0033] In some embodiments, the temperature of the temperature-appropriate treatment is 600° C.-1000° C. Thus, the temperature-appropriate treatment conditions can provide energy for the rearrangement of carbon atoms and doping atoms, so as to form a three-dimensional ordered structure of graphite.
[0034] In some embodiments, the ionic liquid includes at least one of imidazole ionic liquid, pyridine ionic liquid, quaternary ammonium ionic liquid, quaternary phosphine ionic liquid, pyrrolidine ionic liquid, and piperidine ionic liquid. Thus, the ionic liquid can be used as a carbon source material for artificial graphite, wherein the volume of anions and cations is large, the structure is loose, and the interaction between them is low, so the energy required to induce structural changes is less, and the temperature for preparing artificial graphite is lower. The nitrogen and phosphorus elements in the aforementioned ionic liquids can be used as doping elements in artificial graphite, connected to carbon atoms through chemical bonds, and adjust the molecular structure of artificial graphite.
[0035] In some embodiments, the imidazole ionic liquid includes at least one of 1-methylimidazolium chloride, 1-methylimidazolium tetrafluoroborate, and N-methylimidazolium bis(trifluoromethanesulfonyl)imide. Thus, the cation of the imidazole ionic liquid contains an imidazole ring structure, which can provide a carbocyclic structure, and the anion thereof includes at least one of a halogen anion, a borate ion, and a dihydrogen phosphate ion, and the anion can provide a doping element atom.
[0036] In some embodiments, the pyridinium ionic liquid includes at least one of N-ethylpyridinium chloride, N-ethylpyridinium hexafluorophosphate, propylpyridinium chloride, and N-butylpyridinium acetate. Thus, the cation of the pyridinium ionic liquid contains a pyridine ring structure, which can provide a carbon ring structure for preparing artificial graphite, and its anion includes at least one of an anion, a borate ion, and a dihydrogen phosphate ion, and the anion can provide doping element atoms.
[0037] In some embodiments, the heating rate of the temperature treatment is 1°C / min-5°C / min. Therefore, when the heating rate of the temperature treatment is within the above range, the carbon atoms in the carbon source material can be rearranged more fully, and the perfect development of the graphite layered stacking structure can be achieved.
[0038] In some embodiments, the temperature-adaptive treatment reaches a constant temperature by heating, wherein the heating rate of the temperature-adaptive treatment is 3°C / min.
[0039] In some embodiments, the temperature treatment is heated to a constant temperature, wherein the temperature treatment is maintained at a constant temperature for 2 hours to 4 hours. Thus, the layered graphite structure formed by the graphitization process of the carbon source material can be further stabilized, and an artificial graphite with an ordered three-dimensional structure can be prepared.
[0040] In some embodiments, after the pulverization process, the Dv50 particle size of the artificial graphite is 9 μm-13 μm. Thus, the particle size of the prepared artificial graphite is within the aforementioned range, and it has a higher compaction density as a negative electrode material for a battery.
[0041] In some embodiments, the Dv10 of the artificial graphite is 5 μm-7 μm.
[0042] In some embodiments, the Dv90 of the artificial graphite is 15 μm-22 μm.
[0043] In some embodiments, the Dv99 of the artificial graphite is 23 μm-28 μm.
[0044] In some embodiments, it further comprises: before the temperature treatment, the ionic liquid is mixed with the coke material, wherein the mass ratio of the ionic liquid to the coke material is (1-5): 1, and the coke material comprises at least one of coal-based coke, oil-based coke, and bio-based carbon material. Thus, the ionic liquid can also be used as a template during the graphitization process to induce the rearrangement of carbon atoms in the disordered coke material. At the same time, the addition of coke material can reduce the amount of ionic liquid in the carbon source material and control the manufacturing cost of artificial graphite. The bio-based source of the bio-based carbon material in the coke material includes at least one of algae, herbaceous agricultural and forestry plants, and microorganisms. When the mass ratio of the ionic liquid to the coke material is within the aforementioned range, the ionic liquid can play a better template role, and introduce doping elements to regulate the interlayer spacing and structure of the artificial graphite.
[0045] In some embodiments, the mass ratio of the ionic liquid to the coke material is (1-3):1.
[0046] In some embodiments, reference Figure 2 , further comprising: before the ionic liquid is mixed with the coke material, the coke material is purified. Thus, the quinoline insolubles and impurities in the coke material can be removed by distillation, centrifugation, solvent method, and modification method. The quinoline insolubles and impurities include inorganic substances and organic substances. Among them, inorganic substances cannot be converted into artificial graphite through the graphitization process. During the temperature treatment process, their presence will cause gaps or holes that affect the structural integrity of the artificial graphite; and the organic substances therein include organic compounds with an amorphous chaotic layer microcrystalline structure and a high degree of polycondensation. During the temperature treatment process, their tight molecular structure will affect the rearrangement of carbon atoms therein into a graphite structure. Therefore, by removing the above-mentioned substances in the coke material through purification treatment, and then mixing it with the ionic liquid, the structure of the prepared artificial graphite can be controlled and optimized.
[0047] In some embodiments, the mixing treatment includes ball milling, wherein the rotation speed of the ball milling is 400rpm-800rpm, and the mixing treatment time is 1h-3h. Thus, the ionic liquid and the coke material can be fully contacted and infiltrated to form a homogeneous mixture. In the homogeneous mixture, there is an intermolecular force and / or electrostatic effect between the ionic liquid and the coke material, and different carbon source materials are fully mixed, which is conducive to the occurrence of graphitization during the temperature treatment process and the increase of the graphitization rate.
[0048] In a second aspect of the present application, the present application proposes an artificial graphite, which is prepared by the method proposed in the present application.
[0049] The artificial graphite proposed in this application has a relatively regular layered three-dimensional structure and a relatively balanced particle size distribution, and a higher compaction density can be achieved when preparing the negative electrode material layer. At the same time, the doping elements in the artificial graphite make it have more ion active sites, so the artificial graphite has better specific capacity and conductivity as a negative electrode material for batteries.
[0050] In a third aspect of the present application, the present application proposes a negative electrode plate, comprising: the artificial graphite described in the present application.
[0051] The negative electrode plate comprises a negative electrode current collector and a negative electrode material layer, wherein the negative electrode material layer comprises the artificial graphite described in the present application. Therefore, the negative electrode plate proposed in the present application has good electrical performance and cycle performance.
[0052] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0053] Example 1
[0054] S1: subjecting 1-butyl-3-methylimidazolium acetate ionic liquid to a suitable temperature treatment, wherein the heating rate is 2°C / min, the temperature is raised to 800°C, and the temperature is kept constant for 3 hours to obtain an artificial graphite precursor;
[0055] S2: crushing the artificial graphite precursor to obtain artificial graphite.
[0056] Example 2
[0057] S1: 1-butyl-3-methylimidazolium acetate ionic liquid and asphalt were mixed in a ratio of 3:1 and ball-milled at a speed of 500 r / min for 3 h. The mixture was subjected to a suitable temperature treatment at a heating rate of 2 °C / min to 800 °C for 3 h to obtain an artificial graphite precursor.
[0058] S2: crushing the artificial graphite precursor to obtain artificial graphite.
[0059] Example 3
[0060] Implementation 4 is consistent with Example 1, except that the temperature of the temperature treatment is 1000°C.
[0061] Example 4
[0062] Implementation 5 is consistent with Example 1, except that the temperature of the temperature treatment is 1200°C.
[0063] Comparative Example 1
[0064] S1: purifying the asphalt, removing impurities, granulating and then performing appropriate temperature treatment, wherein the heating rate is 5°C / min, the temperature is raised to 2500°C, and the constant temperature time is 3h to obtain an artificial graphite precursor;
[0065] S2: crushing the artificial graphite precursor to obtain artificial graphite.
[0066] Test method:
[0067] The artificial graphite obtained in the example was assembled into a button battery, and its initial efficiency and capacity were tested.
[0068] Graphitization degree test: Calculate the graphite material d by XRD 002 The value is further calculated as follows: degree of graphitization (%) = (3.44-d 002 ) / (3.44-3.354).
[0069] First efficiency test:
[0070] 0.2C reversible gram capacity: After the above-mentioned power-off test of 0.1C charging point capacity, set the current to 0.2C and cycle 3 times.
[0071] 0.1C charge and discharge test: The button battery prepared from the artificial graphite in Example 1 was tested. The test results are shown in Figure 3 .
[0072] The content of each element in the sample was tested by elemental analysis, and the content of P element was obtained by subtracting the content of other elements: Example 1, Example 4, and Example 5 were tested for the content of doped elements, and the results are shown in Table 2.
[0073] Test results:
[0074] Table 1
[0075]
[0076] As can be seen from Table 1, in Example 1 of the present invention, the graphitization degree and the first efficiency of the artificial graphite prepared at an appropriate temperature treatment temperature of 800°C are equivalent to the graphitization degree and the first efficiency of the artificial graphite prepared at 2500°C in Comparative Example 1, and the reversible gram capacity of Example 1 is improved relative to that of Comparative Example 1. Therefore, the method for preparing artificial graphite proposed in the present application optimizes the performance of the prepared artificial graphite material under the premise of saving energy and reducing production equipment requirements and costs. The reversible gram capacity of Example 2 (appropriate temperature treatment temperature of 800°C) and Example 3 (appropriate temperature treatment temperature of 1000°C) are better than those of Comparative Example 1 (appropriate temperature treatment temperature of 2500°C); the first efficiency of Example 4 (appropriate temperature treatment temperature of 1200°C) is better than that of Comparative Example 1 (appropriate temperature treatment temperature of 2500°C). Since the method proposed in the present application prepares artificial graphite under suitable temperature treatment conditions at a relatively low temperature, the prepared artificial graphite still contains O atoms and H atoms, has a high degree of disorder, a wide spacing between carbon layers, a fast lithium ion diffusion rate, and many active sites on the carbon layer surface for lithium ion embedding. Therefore, the artificial graphite proposed in the present application has excellent fast charging performance.
[0077] Table 2
[0078] Optimal temperature for treatment N content / wt% P content / wt% 800℃ 5.40% 8.70% 1000℃ 3.21% 5.40% 1200℃ 0.93% 1.34%
[0079] It can be seen from the data in Table 2 that within the temperature range of the appropriate temperature treatment, the lower the treatment temperature, the higher the content of nitrogen and phosphorus in the artificial graphite.
[0080] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0081] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0082] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing artificial graphite, characterized in that: include: The ionic liquid is subjected to a suitable temperature treatment to obtain a suitable temperature treatment of an artificial graphite precursor; The artificial graphite precursor is pulverized to obtain the artificial graphite, wherein the artificial graphite is doped with nitrogen in an amount of 0.5wt%-6wt% and with phosphorus in an amount of 1wt%-9wt%.
2. The method according to claim 1, characterized in that The temperature of the temperature treatment is 600°C-1000°C; and / or, The ionic liquid includes at least one of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphine ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.
3. The method according to claim 2, characterized in that The imidazole ionic liquid includes at least one of 1-methylimidazolium chloride, 1-methylimidazolium tetrafluoroborate, and N-methylimidazolium bis(trifluoromethanesulfonyl)imide; The pyridinium ionic liquid includes at least one of N-ethylpyridinium chloride, N-ethylpyridinium hexafluorophosphate, propylpyridinium chloride, and N-butylpyridinium acetate.
4. The method according to claim 1, characterized in that: The temperature treatment is carried out by heating up to a constant temperature, wherein: The heating rate of the temperature treatment is 1°C / min-5°C / min; and / or, The constant temperature time of the temperature treatment is 2h-4h.
5. The method according to any one of claims 1 to 4, characterized in that: After the pulverization process, the Dv50 particle size of the artificial graphite is 9 μm-13 μm.
6. The method according to any one of claims 1 to 4, characterized in that: Further including: Before the temperature treatment, the ionic liquid is mixed with the coke material, wherein the mass ratio of the ionic liquid to the coke material is (1-5):1, and the coke material includes at least one of coal-based coke, oil-based coke, and bio-based carbon material.
7. The method according to claim 6, characterized in that Further including: Before the ionic liquid is mixed with the coke material, the coke material is purified.
8. The method according to claim 6, characterized in that The mixing process includes ball milling, wherein the rotation speed of the ball milling is 400 rpm-800 rpm, and the time of the mixing process is 1 h-3 h.
9. An artificial graphite, characterized in that: The artificial graphite is prepared by the method according to any one of claims 1 to 8.
10. A negative electrode plate, characterized in that: include: The artificial graphite according to claim 9.
Citation Information
Patent Citations
Biochar / silicon nano-material, preparation method thereof and application of biochar / silicon nano-material as negative electrode of lithium ion battery
CN113270580A
Preparation method of graphite-based negative electrode material, graphite-based negative electrode material and application of graphite-based negative electrode material
CN115321531A